A study on electronic financial records management in the public sector / Nurussobah Hussin, Mohd Nazir Ahmad and Wan Satirah Wan Mohd Saman - Hussin, Nurussobah; Ahmad, Mohd Nazir; Wan Mohd Saman, Wan Satirah (2007)
This study aims to examine the management of paper based records and how the paper based system influence the electronic records management, to identify whether the accountability, authenticity and integrity of electronic financial records is considered by the public sector, and to determine the policy and standards for electronic financial records care in public sector and the compliance of the standard. Three instruments namely questionnaires; guided interview and content analysis checklist were used in the process of data collection. A qualitative semi structured interviews were held with key players involved in managing financial records in the finance and IT Department in Accountant General Department and National Audit Department. A number of variables on records management system and practices were also set out in the questionnaires which were distributed to a number of middle management staff. The result of the study revealed that the organization does not have enough skilled staffs to meet organization's records management requirement. The findings also demonstrate that the paper-based records gave moderate influenced to the electronic records in term of policy, decision-making, maintenance, preservation, transfer and disposition. The finding will be useful for the policy makers to make decision for better records management practice in public agencies in Malaysia, among others, whether to impose training to the existing staff who manage record or to adopt full time records manager to guarantee a proper records management system being carried out in the organizations.